Cancer statistics, 2018 - Siegel, Rebecca L.; Miller, Kimberly D.; Jemal, Ahmedin (CA: a cancer journal for clinicians, 2018)
Each year, the American Cancer Society estimates the numbers of new cancer cases and deaths that will occur in the United States and compiles the most recent data on cancer incidence, mortality, and survival. Incidence data, available through 2014, were collected by the Surveillance, Epidemiology, and End Results Program; the National Program of Cancer Registries; and the North American Association of Central Cancer Registries. Mortality data, available through 2015, were collected by the National Center for Health Statistics. In 2018, 1,735,350 new cancer cases and 609,640 cancer deaths are projected to occur in the United States. Over the past decade of data, the cancer incidence rate (2005‐2014) was stable in women and declined by approximately 2% annually in men, while the cancer death rate (2006‐2015) declined by about 1.5% annually in both men and women. The combined cancer death rate dropped continuously from 1991 to 2015 by a total of 26%, translating to approximately 2,378,600 fewer cancer deaths than would have been expected if death rates had remained at their peak. Of the 10 leading causes of death, only cancer declined from 2014 to 2015. In 2015, the cancer death rate was 14% higher in non‐Hispanic blacks (NHBs) than non‐Hispanic whites (NHWs) overall (death rate ratio [DRR], 1.14; 95% confidence interval [95% CI], 1.13‐1.15), but the racial disparity was much larger for individuals aged <65 years (DRR, 1.31; 95% CI, 1.29‐1.32) compared with those aged ≥65 years (DRR, 1.07; 95% CI, 1.06‐1.09) and varied substantially by state. For example, the cancer death rate was lower in NHBs than NHWs in Massachusetts for all ages and in New York for individuals aged ≥65 years, whereas for those aged <65 years, it was 3 times higher in NHBs in the District of Columbia (DRR, 2.89; 95% CI, 2.16‐3.91) and about 50% higher in Wisconsin (DRR, 1.78; 95% CI, 1.56‐2.02), Kansas (DRR, 1.51; 95% CI, 1.25‐1.81), Louisiana (DRR, 1.49; 95% CI, 1.38‐1.60), Illinois (DRR, 1.48; 95% CI, 1.39‐1.57), and California (DRR, 1.45; 95% CI, 1.38‐1.54). Larger racial inequalities in young and middle‐aged adults probably partly reflect less access to high‐quality health care. CA Cancer J Clin 2018;68:7‐30. © 2018 American Cancer Society.